Psychological Effects of Poverty on Time Preferences. Issue 638 (1st February 2021) - Bartoš, Vojtěch; Bauer, Michal; Chytilová, Julie; Levely, Ian
Abstract: We test whether an environment of poverty affects time preferences through purely psychological channels. We measured discount rates among farmers in Uganda who made decisions about when to enjoy entertainment instead of working. To circumvent the role of economic constraints, we experimentally induced thoughts about poverty-related problems, using priming techniques. We find that thinking about poverty increases the preference to consume entertainment early and to delay work. Using monitoring tools similar to eye tracking, a novel feature for this subject pool, we show that this effect is unlikely to be driven by less careful decision-making processes.